2009
DOI: 10.2215/cjn.02230409
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gestational Age and Birth Weight on Amikacin Clearance on Day 1 of Life

Abstract: Background and objectives: Intrauterine growth restriction (IUGR) and prematurity are associated with a low nephron endowment. It can therefore be expected that neonates who are born premature and/or after IUGR have a lower GFR. Measurement of GFR in neonates is difficult, but the clearance of amikacin has been proven to be a reliable marker. We hypothesized that amikacin clearance is lower after IUGR or premature birth as a marker of low nephron endowment.Design, setting, participants, & measurements: Amikaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 41 publications
3
32
0
Order By: Relevance
“…Indeed, GFR extrapolated from Amikacin clearance on day 1 of life, preceding any compensatory adaptation, was significantly reduced in premature and LBW infants compared to term controls 67 . GFR measured by inulin clearance was significantly lower at age 7.6 years in children who had been premature and had severe growth restriction compared to non growth restricted controls 41 .…”
Section: Renal Function Birth Weight and Nephron Massmentioning
confidence: 92%
“…Indeed, GFR extrapolated from Amikacin clearance on day 1 of life, preceding any compensatory adaptation, was significantly reduced in premature and LBW infants compared to term controls 67 . GFR measured by inulin clearance was significantly lower at age 7.6 years in children who had been premature and had severe growth restriction compared to non growth restricted controls 41 .…”
Section: Renal Function Birth Weight and Nephron Massmentioning
confidence: 92%
“…119 In longer term follow-up of children with very low birth weight (VLBW; Ͻ1000 g), serum creatinine was higher and GFR lower compared with age-matched NBW children at 6 to 12 years. 120 A stronger association was found using cystatin C in children, suggesting that creatinine-based formulas underestimate the impact of birth weight on GFR.…”
Section: Measures Of Renal Functionmentioning
confidence: 98%
“…Previous studies indicated that amikacin CL was in the range of 31.3 -91 ml/h·kg, while half-life (t 1/2 ) was in the range of 4 -9.3 h (8, 11 -13, 21). High interindividual variability in amikacin pharmacokinetics was previously observed, and it was described in detail in pre-term neonates (9,11,22). In pre-term neonates, weight and gestational and/or neonatal age significantly contributed to amikacin pharmacokinetic variability (9,10,23).…”
Section: Introductionmentioning
confidence: 82%